Strategy For Supporting The Strengthening Of Religious Moderation Among Students At Dayah Markaz Al-Ishlah Al-Aziziyah Banda Aceh - Hayati Hayati; Nurbayani Nurbayani; Nadia Tri Yanty Seroja; Mohammad Eisa Ruhullah (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2025)
The problems in strengthening religious moderation at Dayah Markaz Al-Ishlah Al-Aziziyah are related to challenges in integrating the values of moderation, especially overcoming internal and external differences in religion and the application of the principle of non-violence among students. The purpose of the study is to be able to improve this strengthening, a suitable and appropriate mentoring pattern is needed considering that the students of the Markaz Al-Ishlah Al-Aziziyah Dayah come from orphans who are victims of the conflict in Aceh and orphans who are victims of natural disasters. This service method uses Participation Action Research (PAR). The number of mentoring samples was 32 students (10%) and 2 ustadz/ustazah and 1 dayah leader. The results of the study showed that 1). The Mentoring Pattern for Strengthening Religious Moderation at the Markaz Al-Ishlah Al-Aziziyah Dayah Students in Banda Aceh is that the dayah leader builds a pattern of strengthening religious moderation based on the values of family, brotherhood, and equality among fellow students. This pattern includes close relationships like parents and children, siblings and older siblings, and grandparents. 2). The materials for mentoring the strengthening of religious moderation in students of Dayah Markaz Al-Ishlah Al-Aziziyah Banda Aceh are First, Balance (Tawazun). Second, Tolerance (Tasamuh). Third, Justice (Adl). Fourth, Humanity (Insaniyah). Fifth, Anti-Violence (Laa Unf). Sixth, Openness (Infitah), which invites to be open to changes in the times without sacrificing the basic principles of religion, and Seventh, Deliberation (Syura).